Frame Analysis of Political Texts - Dyachuk, Nataliia (East European Journal of Psycholinguistics, 2017)
The article outlines the study of political texts from psycholinguistic perspectives. The research generalizes and empirically verifies a psycholinguistic approach to the study of political discourse and focuses on frame analysis, one of the most powerful psycholinguistic techniques. Frame structure embraces conceptual components that allow accumulating information from different sources. The public speeches of two great Ukrainian and American political leaders Viktor Yushchenko and Barack Obama were the principal sources of the analysis. Frame analysis was applied to study cross-cultural peculiarities that depict national nature of two cultures. Data analysis shows that discourse of the Ukrainian leader is mostly focused on categories such as people, power, liberty. The discourse of the American leader contains categories such as economy, money, people, psychological constructs. The results show that people have become top-priority for V. Yushchenko. They are the people the Ukrainian politician addresses, believes and trusts. V. Yushchenko also carries about freedom, independence and liberty of any Ukrainian citizen. B. Obama is deeply concentrated on economy and finance of his country. It has become obvious that he is ready to implement the set of reforms for the country to thrive. The category of psychological constructs shows that the American politician is full of respect and proud for his country ant population. The radical variety of two speeches is caused by different economic conditions, values and mentality of two cultures and personal purposes and objectives of two representatives. References Алимурадов О. Картины языка музыки. Функционально-семантическая характеристика современной английской музыкальной лексики: когнитивнофреймовый подход. М.: КРАСАНД, 2009. Alimuradov, O. (2009). Kartiny Yazyka Muzyki. Funktsional’no-Semanticheskaya Kharakteristika Sovremennoy Angliyskoy Muzykal’noy Leksiki: Kognitivno-Freymovyy Podkhod [Pictures of the Language of Music. Functional-Semantic Characteristics of Modern English Musical Vocabulary: Cognitive-Frame Approach]. Moscow: KRASAND. Minsky, M. (1975). A framework for representing knowledge. In: The Psychology of Computer Vision (pp. 211-277), P.H. Winston (ed.). New York: McGraw-Hill. Никонова Ж. Теория фреймов в лингвистических исследованиях. СПб: СпбГУ, 2006. Nikonova, Zh. (2006). Teoriya Freymov v Lingvisticheskikh Issledovaniyakh [The Theory of Frames in Linguistic Studies]. S.-Petersburg: St. Petersburg State University. Никонова Ж. Основные этапы фреймового анализа речевых актов // Вестник Нижегородского университта им. Н. И. Лобачевского. 2008. № 6. С. 224–228. Nikonova, Zh. (2008). Osnovnyye etapy freymovogo analiza rechevykh aktov (na materiale sovremennogo nemetskogo yazyka) [The main stages of frame analysis of speech acts (on the basis of modern German language]. Vestnik Nizhegorodskogo Universiteta im. N. I. Lobachevskogo, 6, 224–228 Шейгал Е. Семиотика политического дискурса. М.: Гнозис, 2004. Sheygal, Ye. (2004). Semiotika Politicheskogo Diskursa [The Semiotics of Political Discourse]. Moscow: Gnozis. Стернин И. Методика исследования структуры концепта. Воронеж, 2001. Sternin, I. (2001). Metodika Issledovaniya Struktury Kontsepta [Methodology for Studying the Structure of the Concept]. Voronezh: Voronezh University. Засєкіна Л., Засєкін С. Психолінгвістична діагностика. Луцьк: Вежа, 2008. Zasiekina, L, Zasiekin, S (2008). Psyholinhvictychna Diahnostyka [Psycholinguistic Diagnostics]. Lutsk: Vezha. Sources Obama, B. (2007) Barack Obama’s campaign speech. Retrieved from http://www.theguardian.com/world/2007/feb/10/barackobama. Ющенко В. Слухай своє серце, керуйся своїм розумом!// Високий замок. № 185(3). Yushchenko, V. (2004) Slukhay svoye sertse, keruysya svoyim rozumom! [Listen to your heart; be guided by your mind!]. Vysokyy Zamok, 185, 3.